Course of residual symptoms according to the duration of euthymia in remitted bipolar patients. (30th March 2016) - Samalin, L.; Reinares, M.; de Chazeron, I.; Torrent, C.; Bonnin, C. M.; Hidalgo‐Mazzei, D.; Murru, A.; Pacchiarotti, I.; Geoffroy, P. A.; Bellivier, F.; Llorca, P. M.; Vieta, E.
Abstract : Objective: Although many studies showed the negative impact of residual symptoms on the course of bipolar disorder (BD), there is a need to examine potential differences in residual symptoms according to the duration of euthymia in remitted BD patients. Method: This was a large cross‐sectional study of 525 euthymic BD out‐patients. A multivariate analysis of covariance was conducted to compare depressive and manic residual symptoms, sleep disturbances and cognitive complaints among three patient groups on the basis of duration of euthymia (A. 6 months to <1 year; B. 1 year to <3 years; C. 3 years to ≤5 years). Results: A significant difference between the three groups was found in residual symptoms [Pillai's Trace: F (8942) = 4.659, P  < 0.001]. Tukey post hoc analysis indicated that patients from Group C presented lower residual depressive symptoms, higher sleep quality and better perceived cognitive performance compared with Group A. Group B also presented better sleep and cognitive outcomes than Group A. In addition, Group C showed the lowest incidence of functional impairment. Conclusion: This study suggests that the intensity of residual symptoms and functional impairment in remitted BD patients is negatively related to the duration of euthymia.